P3.056 Prevalent Human Papillomavirus in Tanzanian Adolescent Girls Who Report Not Having Passed Sexual Debut. (13th July 2013) - Houlihan, C F; Sanjosé, S de; Baisley, K; Changalucha, J; Ross, D; Kapiga, S; Godinez, J M; Bozicevic, I; Hayes, R; Watson-Jones, D
Abstract : Objectives: The HPV vaccine is recommended for girls prior to sexual debut since it is most effective if administered prior to HPV acquisition. Little research has been conducted in high HPV-prevalence countries regarding HPV infection in girls who report not having passed sexual debut. We present the HPV prevalence in girls enrolled in a cohort study in Mwanza, Tanzania, who report not having passed sexual debut. Methods: Girls aged 15–16 years who had previously attended 82 randomly selected primary schools were enrolled and underwent a face-to-face interview on socio-demographic variables, sexual behaviour and intra-vaginal practises. A nurse-assisted self-administered vaginal swab was collected. Swabs were tested for 13 high-risk (HR) and 24 low-risk (LR) HPV genotypes using the Roche LINEAR ARRAY ® HPV genotype test. Results: Of 1555 female primary school attenders, 1177 (76%) were located, of whom 801 were aged 15 or 16 years. Of these, 628 (78%) consented to eligibility screening and 480 girls who reported not having passed sexual debut were enrolled. B-globin negative results (to ensure sample quality) were excluded (N = 6). HPV was detected in 40/474 (8.4%; 95% C-I: 5.9–11.0) girls. The most common genotype was HPV42, detected in 9/474 (1.9%; 95% CI: 0.9–3.7). HR genotypes were detected in 5.3% (95% CI: 3.5–7.8). Overall, 50% of girls with HPV had infection with > 1 genotype. In multivariate analysis, only intra-vaginal cleansing (practised by 21.0%) was associated with HPV detection (aOR = 3.16.95% CI: 1.46–6.85) Conclusion: In this cohort of adolescent Tanzanian girls, we found a high HPV prevalence prior to self-reported sexual debut, which was associated with intra-vaginal cleansing. This is likely to reflect under-reporting of sexual activity. However, vaginal HPV could be acquired during vaginal cleansing. Potential HPV transmission through genital hygiene practises or other practises (e.g.female genital mutilation or masturbation) should be explored to determine the possibility of HPV acquisition prior to first sex, which may have implications for vaccination programmes.